Building Immersive Library Environment to Access Virtual Reality Content A Proposed Framework Model - Roy, Samrat Guha; Kanjilal, Uma; Sutradhar, B.; Jalal, S.K. (DESIDOC Journal of Library & Information Technology, 2022)
Immersive environments refer to a computer-simulated 3-dimensional virtual world. Libraries worldwide have been adopting and implementing new immersive technologies to enhance users’ experience and learning. The Central Library of IIT Kharagpur offers (i) web-based augmented reality (WebAR), (ii) virtual reality (VR), and (iii) data visualisation immersive services. This research investigates the users’ perceptions on factors that influence their satisfaction with WebAR/VR services. The study surveyed 135 random users to note their immersive library experience; out of them, only 100 users responded to our survey. The results show that 90 per cent of the respondents were satisfied with our services. Secondly, the respondents revealed that data privacy, health, and safety were some of the critical factors that influenced their satisfaction. Further, 14 per cent were apprehensive in terms of their health & safety. In fact, these users reported vision problems, disorientation, dizziness, sweating, and nausea. Based on the data collected, we prepared a framework, using The DELOS DL reference model for information delivery, along with educational and research activities. We believe that this study would lend crucial insights to academic libraries that may be planning to adopt and implement AR/VR as part of their immersive environment.